Identification of the preferred teaching styles for Physical Education teachers at secondary education - Espada Mateos, Maria; Pineño, Pedro Julio (Journal of Learning Styles, 2020)
The teaching styles in physical education is a pedagogical model that provides teachers with alternative options for addressing student diversity and accomplishing multiple goals. The aim of this study was to identify the preferred teaching styles of physical education teachers depending on school type, age, gender and teaching experience at secondary education. A sample of 35 Physical Education teachers of secondary education was involved. It was conducted a non-experimental and transversal research design with quantitative approach and descriptive scope. The results of the study showed that the teaching styles by preference were the traditional character styles followed by cognitive, individualized, participatory and socializing and creative styles. There were not significant differences in relation to school type, age, gender and teaching experience.